2019
DOI: 10.1021/acs.jafc.9b01922
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Study of Novel Antihypertensive Peptides Derived from Cassia obtusifolia Seeds

Abstract: Antihypertensive peptides were screened from thermolysin hydrolysate of Cassia obtusifolia seeds (Jue Ming Zi) using two independent bioassay-guided fractionations, reversed-phase high-performance liquid chromatography (RP-HPLC), and strong cation-exchange (SCX) liquid chromatography coupled with angiotensin I-converting enzyme (ACE) inhibitory assay. The identical peptide in the most active RP-HPLC and SCX fractions was simultaneously de novo sequenced as FHAPWK with high-resolution mass spectrometry. FHAPWK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
(67 reference statements)
1
40
0
Order By: Relevance
“…Therefore, a vital step in studying bioactive peptides is to know how to make them more efficiently accessible, thereby reducing researching time and finances to screen and eliminate inferior peptides. According to the different characters of each peptide such as the molecular weight, hydrophobicity, and other physicochemical properties, several orthogonal bioassay-guided methods were applied individually as well as the combination of two or three chromatography techniques which were utilized [ 4 , 26 , 27 , 28 , 29 ]. To fractionate SSTY GI hydrolysates, two column chromatography methods (RP and SCX) with different separation mechanisms were performed in parallel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a vital step in studying bioactive peptides is to know how to make them more efficiently accessible, thereby reducing researching time and finances to screen and eliminate inferior peptides. According to the different characters of each peptide such as the molecular weight, hydrophobicity, and other physicochemical properties, several orthogonal bioassay-guided methods were applied individually as well as the combination of two or three chromatography techniques which were utilized [ 4 , 26 , 27 , 28 , 29 ]. To fractionate SSTY GI hydrolysates, two column chromatography methods (RP and SCX) with different separation mechanisms were performed in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Potential peptides were synthesized based on the method reported by Shih et al, [ 28 ] with slight modification. Identified peptide sequences were synthesized starting from C-terminal to the end of N-terminal using Wang resins as the solid support based on the CEM Discover reactor (CEM Microwave Technology Ltd., Buckingham, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, MRM can provide an analysis of multiple peptides in a single LC-MS run. Several studies reported on the application of the MRM method to measure the peptide amount present in food proteins like egg and plants [98,[136][137][138][139].…”
Section: Quantification Of Peptidesmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first report that introduces novel ACE inhibitory peptides from GSPs hydrolysate. Compared to other peptides derived from other food-sourced proteins reported previously, ALVY (IC 50 = 7.03 ± 0.09 µM) showed a remarkable ACE inhibitory activity superior than those generated from other plant seeds, such as Cassia obtusifolia seeds (FHAPWK, IC 50 = 16.8 μM) [ 38 ], barley (FQLPKF, GFPTLKIF, NFLARF, and ALRYFM IC 50 values ranged from 28.2 to 200 μM) [ 39 ], bitter melon seeds (VSGAGRY, IC 50 = 8.6 μM) [ 40 ], hemp seeds (WVYY, WYT, SVYT, and IPAGV, IC 50 values ranged from 27 to 574 μM) [ 41 ], and wheat germ (QV, NPPSV, and VEW, IC 50 values ranged from 26.8 to 115.2 μM) [ 42 ].…”
Section: Resultsmentioning
confidence: 92%